Gaming Disorder Seen Through the Prism of Dual Diagnosis: Prevalence and Associated Factors - Barrangou-Poueys-Darlas, Malcolm; Cabelguen, Clémence; Garrouste, Vincent; Leboucher, Juliette; Rocher, Bruno; Challet-Bouju, Gaëlle; Grall-Bronnec, Marie (Frontiers in Psychiatry, 2022)
Introduction: Dual diagnosis (DD) is defined as the co-occurrence of at least a psychiatric disorder and at least an addictive disorder. Most studies about DD considered substance use disorders. In 2018, gaming disorder (GD) was recognized as a formal disorder and integrated into the category of addictive disorders in the 11th version of the International Classification of Diseases. Our objectives were to measure DD prevalence among GD patients and to assess factors associated with the presence of DD. Method: As part of the EVALuation of behavioural ADDictions (EVALADD) cohort, 92 patients with GD were included in the present study. Psychiatric disorders, including anxiety, mood, and psychotic disorders, were explored with the Mini International Neuropsychiatric Interview (MINI 5.0.0). Probable adult attention-deficit/hyperactivity disorder (ADHD) was screened with the Wender Utah Rating Scale (WURS) in childhood and with the ADHD Self-Report Scale-V1.1 (ASRS) in adulthood. Finally, personality was assessed using the 125-item version of the Temperament and Character Inventory (TCI-125), motives for gaming with the Videogame Motives Questionnaire (VMQ) and attachment styles with the Relationship Scales Questionnaire (RSQ). To measure the prevalence of DD among GD patients, we considered the occurrence of current GD with current anxiety, mood, or psychotic disorders, or with probable current ADHD. We also performed a multivariate analysis to identify independent factors associated with DD. Results: More than half (55.4%) of GD patients suffered from DD. We found a high prevalence of probable ADHD (38%) and anxiety disorders (29% suffering from generalized anxiety disorder, social, agoraphobia or panic disorder). Four variables were significantly associated with DD: suicidal thoughts (odds ratio [OR] = 6.83, 95% confidence interval [95%CI] [1.66–28.09]), VMQ "coping" scores (OR=1.18, 95%CI[1.01–1.38]), TCI-125 “harm avoidance" scores (OR=1.04, 95%CI[1.01–1.07]) and “novelty seeking” scores (OR=1.03, 95%CI[1.00–1.06]). Discussion: The prevalence of certain psychiatric disorders among GD patients far exceeded that observed in the general population. Both ADHD and suicidal ideations should particularly be screened among GD patients. Specific interventions targeting personality dimensions associated with DD but also on the management of negative affect should represent new treatment opportunities.